Social anxiety and smartphone addiction among college students: the mediating role of loneliness - Zhou, Xingping; Feng, Baoan (Frontiers in Psychiatry, 2025)
Background and aimsAs one of the by-products of smartphone proliferation, smartphone addiction, has negatively affected college students’ academics and well-being, making it a critical issue for educators to address. This study explored how social anxiety and loneliness predict smartphone addiction, adding to prior research in this area.Design, setting and participantsA cross-sectional research design and a random sampling method were employed to collect data from 2,113 Chinese college students in February 2025. The average age of participants was 19.9 ± 1.23 years (age range: 18–25 years).MeasurementsAll participants provided their data on demographic characteristics, social anxiety (assessed using the Revised Social Anxiety Subscale of the Self-Consciousness Scale), smartphone addiction (measured via the Cell Phone Addiction Scale), and loneliness (evaluated with the 6-item De Jong Gierveld Loneliness Scale). Mediation analyses were conducted using Hayes’ PROCESS macro (v4.1) in SPSS (v24). Specifically, Model 4 implemented 5,000 bootstrap resampling repetitions to calculate indirect effects, deriving 95% bias-corrected confidence intervals through percentile-based resampling.FindingsStatistical analyses showed that social anxiety was positively correlated with loneliness (r = 0.269, p < 0.001), smartphone addiction (r = 0.158, p < 0.001), and gender (r = 0.058, p < 0.01), and loneliness was positively correlated with smartphone addiction (r = 0.246, p < 0.001) and age (r = 0.046, p < 0.05). Social anxiety predicted smartphone addiction (β = 0.309, p < 0.001, 95%CI = [0.222, 0.396]), and loneliness predicted smartphone addiction (β = 0.406, p < 0.001, 95%CI = [0.222, 0.396]), with loneliness partially mediating their relationship (effect = 0.123, 95%CI = [0.092, 0.157]).ConclusionsSocial anxiety is significantly correlated with smartphone addiction, and loneliness partially mediating their relationship. Reducing loneliness can prevent smartphone addiction among college students with social anxiety.